Pengaruh Pemberian Kulit Ari Biji Kedelai Hasil Fermentasi dengan Aspergillus niger dalam Ransum terhadap Bobot Karkas Ayam Pedaging - Nelwida, Nelwida (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2011)
The  study  was  conducted  to  determine  the  effect  of  feeding  fermented  epidermis  of  soybean  sedd with Aspergillus niger as substitution of maize and soybean meal in the ration on carcass weight of broiler . The study was carried out in Laboratory of Feed Science to analyze the nutrient content of feedstuffs and in the Cages under Laboratory of Poulty Nutrition, Faculty of Animal Science, University of Jambi for feeding trial.  The  experiment  was  designed  to  Completely  Randomized  Design  (CRD)  with  5  treatments  and  4 replications. Feeding trial used 100 DOC starins MB-202 P fed basal ration with different level of fermented epidermis  of  soybean  seed  with Aspergillus  niger as  treatment.  The  treatments  were  R0  (basal  ration without fermented epidermis of soybean seed with Aspergillus niger ), R1 (basal ration containing 10 % of fermented epidermis of soybean seed with Aspergillus niger), R2 (basal ration containing 20 % of fermented epidermis  soybean  seed  with Aspergillus  niger),  R3  (basal  ration  containing  30  %  of fermented  epidermis soybean seed with Aspergillus niger) and R4 (basal ration containing 40 % of fermented epidermis soybean seed with Aspergillus niger). Parameters measured were feed consumption, body weight and carcass weight. Result  of  this  study  showed  that  substitution of maize    and  soybean  meal  with  fermented  epidermis  of soybean seed using Aspergillus niger significantly (P<0,05) influenced feed consumption, body weight and absolute carcass weight but no significantlt (P>0,05) on percentage carcass weight of broiler. It is concluded that fermented epidermis of soybean seed with Aspergillus niger could be mixed in to the ration up to 40 % to substitute maize and soybean meal and it was not negative influenced on carcass weight of broiler.